Do Acquisitions Create Value for Acquirer Companies in India? An Empirical Study - Ranju, P. K.; Mallikarjunappa, T. (Indian Journal of Research in Capital Markets, 2017)
This paper examined the shareholder wealth effects of acquisition announcements in India using a sample of 349 acquisition announcements made by 219 BSE 500 companies during the period from January 1, 2005 to December 31, 2014. We employed event study methodology to measure shareholder wealth effects of acquirer companies on acquisition announcements. The study found that shareholders of the Indian acquirer companies involved in acquisitions experienced significant abnormal returns of 0.37% on the day of the announcement. We also found negative cumulative average abnormal returns (CAARs) during the longer event window of 61-day, 41-day, and post-event window of 30 days, and positive CAARs during the event window of 31-day, 21-day, 11-day, 5-day, 3-day, pre-event window of 30 days, and the pre-event window of 20 days. However, CAARs were not significant at the 5% level of significance for any of the event windows except for post-event window of 20 days (+1, +20). We observed significant negative CAAR of 1.21% during the post-event window of 20 days (+1, +20). Hence, we concluded that announcement of acquisitions does not create value for the acquirer company shareholders. Moreover, negative significant CAAR during the post-event window of 20 days (+1, +20) suggested that acquisitions reduce wealth significantly during the post-event period.